2020
DOI: 10.1200/jco.2020.38.15_suppl.e15055
|View full text |Cite
|
Sign up to set email alerts
|

Serine/threonine kinase 11 (STK11) mutations and immunotherapy resistance in patients with non-small cell lung cancer.

Abstract: e15055 Background: There is immune evasion and resistance to checkpoint inhibitors (CPI). Programmed death-ligand 1 (PD-L1) and Tumor mutational burden (TMB) might help us predict response, but we have not yet validated biomarkers that can predict resistance. Mutations (mut) in STK11 can induce epigenetic changes that confer proliferative advantages to cancer cells and preliminary reports have suggested that they can confer resistance to CPI. We investigated the role of STK11 and KRAS mut as markers of poor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…19 It was shown to worsen the treatment outcome in patients receiving both chemotherapy and ICI, though prognostic significance is less pronounced in the cohort of patients receiving ICI. 6,16,20,21 Consequently, STK11 may play both a prognostic and predictive role, which agrees with our results. Since STK11 mutations are frequently observed in PD-L1-low/TMB-low patients 22,23 this marker may provide an additional molecular-defined cohort of patients with NSCLC, which may benefit more from immunotherapy.…”
Section: Resultssupporting
confidence: 92%
“…19 It was shown to worsen the treatment outcome in patients receiving both chemotherapy and ICI, though prognostic significance is less pronounced in the cohort of patients receiving ICI. 6,16,20,21 Consequently, STK11 may play both a prognostic and predictive role, which agrees with our results. Since STK11 mutations are frequently observed in PD-L1-low/TMB-low patients 22,23 this marker may provide an additional molecular-defined cohort of patients with NSCLC, which may benefit more from immunotherapy.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the KRAS p.G12C mutation was observed in the presence of high STK11 mutation levels in this study, as has recently been reported by others in a single treatment center [39]. STK11 mutations have been observed at a high rate in NSCLC and even higher in KRAS mutated NSCLC; the KRAS p.G12C/STK11 co-mutation pattern has been associated with lower overall survival and resistance to immune checkpoint inhibitors [38,[40][41][42][43][44]. KEAP1 mutations were prevalent in the G12C cohort, as well as the other cohorts in this study; although others have reported even higher levels of KEAP1 co-mutation [39].…”
Section: Discussionsupporting
confidence: 85%
“…Many retrospective clinical studies investigated LKB1 mutations as a negative determinant of immunotherapy response ( 50 , 168 170 ). Indeed, patients with non-squamous LKB1 -mutated NSCLC tumors do not respond to ICI or they general have dramatically lower survival and progression-free survival ( 50 , 171 , 172 ). This is true for patients given with ICI both in first-line and second-line treatments, and considering both monotherapy and a combination of two ICIs ( 168 , 173 , 174 ).…”
Section: Lkb1 and Immune Systemmentioning
confidence: 99%